Occurrence of non-native species and their potential impact on plant communities in protected areas in the Brazilian Amazon region - Magalhães, Lana Cynthia Silva (2020)
Abstract. Introduction: There is a large information gap on the occurrence of non-native species and their impacts on native biodiversity in the Amazon region in Brazil. Objective: The objective of this study was to characterize the floristic composition of a protected area in Manaus, Amazonas, and assess the potential impact of non-native invasive species. Methods: A floristic survey was carried out in 30 plots measuring 20 x 20 m with 1 x 1 m subplots. The estimated parameters were density, frequency, dominance, Importance Value Index (IVI), and Environmental Impact of Non-Native Species (IIAE). Results: In total, 8 out of 264 species registered in the tree-shrub layer were not native. A total of 61 species were identified in the herbaceous layer, five of which were non-native. The impact is estimated based on the highest abundance of species of non-native species. Conclusions: The presence of non-native species in the study area is an indication of a potential impact on biodiversity and ecosystem functions.